Desenvolvimento de um sistema de monitoramento em tanques de piscicultura para auxiliar no manejo de tilápias - Bartz, Rafael Luis (2017)
Fish farming has been growing over the years driven by increasing world population. The increasing demand of food production makes it necessary to constantly improve management techniques, increasing production and reducing costs, making the activity sustainable. In this context, the adhesion of technological resources that assist in the management and control of nurseries is very important. The monitoring of water quality is also essential in fish farming, since certain variables, such as temperature, are directly related to the fish metabolism, influencing the amount of feed consumed by them. The acquisition of ration represents up to 79% of the production costs, making it vital to obtain maximum feed conversion. After a survey, that was carried out with a group of fish farmers from the western region of Paraná to investigate whether they consider the quality of water in their nurseries to optimize management, and if they use technological resources in their production process, it was verified that most do not consider the quality of water in their production process, nor do they make use of technological resources to aid in their management. The results of this survey motivated the development of a water quality monitoring system through an autonomous sensorial buoy, linked to a software to support the management of productive nurseries. To test the system and to verify its economic potential, an experiment was carried out for 26 weeks, involving two groups of fifteen tilapias distributed randomly in two tanks, one endowed with the monitoring system, and another not. The process of feeding was based on feeding tables used by the fish farmers interviewed in the survey, with the feeding in the tank with the monitoring system calculated based on the temperature and weight of the animals, while in the other tank the calculation considered only the weight of tilapias. During the experiment, mean weight, amount of feed intake, and standard length were recorded, which were analyzed by means of descriptive statistics, Anderson-Darling normality test and Student's t-test for comparison of independent sample means. The value of feed conversion was also obtained, which was calculated by dividing the amount of feed consumed by each tilapia group by the weight gain acquired by them. As a result, it was observed that the feed conversion in the monitored tank was higher in relation to the unmonitored tank, resulting in a saving of the ration consumption per kilogram (kg) of tilapia produced during the experimental period. It was also observed that there was no significant difference between the average weights and the standard tilapia lengths of the two tanks at the end of the experiment. The sensory buoy and the software connected to it proved to be effective throughout the experiment, showing that they could be installed in real productive nurseries. These results evidenced the economic viability of the proposed monitoring system, making it an excellent alternative for increasing income in fish farming.